2022
DOI: 10.3390/electronics11203301
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Bias Amplification in Graph Neural Network Approaches for Recommender Systems

Abstract: Recommender Systems (RSs) are used to provide users with personalized item recommendations and help them overcome the problem of information overload. Currently, recommendation methods based on deep learning are gaining ground over traditional methods such as matrix factorization due to their ability to represent the complex relationships between users and items and to incorporate additional information. The fact that these data have a graph structure and the greater capability of Graph Neural Networks (GNNs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…It is claimed that the use of the GNN-based method for RS can improve the accuracy of the results [18][19][20]. On the other hand, this enhancement in performance can cause bias and fairness problems [21,22]. As discussed in Section 2.2, the structure of graphs together with the message-passing system inside GNNs can amplify bias problems, leading to unfair outcomes.…”
Section: Bias and Fairness In Gnn-based Rsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is claimed that the use of the GNN-based method for RS can improve the accuracy of the results [18][19][20]. On the other hand, this enhancement in performance can cause bias and fairness problems [21,22]. As discussed in Section 2.2, the structure of graphs together with the message-passing system inside GNNs can amplify bias problems, leading to unfair outcomes.…”
Section: Bias and Fairness In Gnn-based Rsmentioning
confidence: 99%
“…Within this approach, the methods based on graph neural networks (GNNs) perform well in this application domain, although they are still affected by the bias shortcoming. Some studies have shown that graph structures and the used message-passing system inside GNNs promote the amplification of unfairness and other social biases [21,22]. Moreover, in most of the social networks with graph architecture, nodes with similar sensitive attributes are prone to be connected in comparison to other nodes with different sensitive attributes (e.g., young individuals are more likely to start a friendship in social networks).…”
Section: Introductionmentioning
confidence: 99%
“…Fairness helps to mitigate bias, supports diversity, and boosts user satisfaction. In GNN-based systems, which can amplify bias, fairness is crucial for balanced recommendations and optimal performance (Ekstrand et al, 2018 ; Chizari et al, 2022 ; Chen et al, 2023 ; Gao et al, 2023 ).…”
Section: Fairness In Gnn-based Recommender Systemsmentioning
confidence: 99%
“…As mentioned in the introduction, the theory of the spiral of silence is of significant importance in the climate of recommender systems, as the standard for recommendations in different recommendation systems can vary significantly due to various user attributes, such as race, gender, and personality [4].…”
Section: Survey Of Relevant Previous Workmentioning
confidence: 99%